Undiagnosed airflow limitation is common in patients with coronary artery disease and associated with cardiac stress. Issue 1 (29th October 2015) - Ko, Fanny W.S.; Yan, Bryan P.; Lam, Yat‐yin; Chu, Jojo H.Y.; Chan, Ka‐pang; Hui, David S.C.
Abstract: Background and objective: Smoking is a common risk factor for coronary artery disease (CAD) and chronic obstructive pulmonary disease (COPD). We evaluated the prevalence of undiagnosed COPD in patients with CAD and assessed the relationship between airflow obstruction and markers of cardiac stress. Methods: We recruited prospectively consecutive patients aged >40 years without known history of chronic lung disease (e.g. asthma, COPD, bronchiectasis) who had undergone percutaneous coronary intervention (PCI) for obstructive CAD between August 2009 and October 2010. Spirometry was performed and serum ST2, a novel biomarker of cardiomyocyte stress and fibrosis, was measured by enzyme‐linked immunosorbent assay. Results: Among 475 subjects (mean age 64 ± 9.7, range 42–85 years, 87.2% males, 58.5% current or ex‐smokers) who underwent spirometry, 51 (10.7%) had undiagnosed airflow obstruction with FEV1 /FVC ratio <70%. Of these 51 subjects, 14 (2.9%), 23 (4.8%) and 14 (2.9%) had FEV1 ≥80, 50–80 and 30–50% predicted normal, respectively. ST2 level was measured in all the subjects with undiagnosed airflow obstruction and in 290 subjects with normal lung function. There was no significant difference in left ventricular ejection fraction on echocardiogram between subjects with and without airflow obstruction. Patients with severe airflow obstruction had a higher level of cardiac stress marker ST2 than those with mild and moderate airflow obstruction (rho = −0.214, P ≤ 0.001). Conclusion: Undiagnosed airflow obstruction is common among patients with CAD who have undergone PCI. Severity of airflow limitation is associated with increasing cardiac stress. Abstract : Undiagnosed airflow obstruction is common among patients with coronary artery disease who have undergone percutaneous coronary intervention. The level of cardiac stress marker ST2 was positively correlated with spirometric air flow obstruction.